2020
DOI: 10.5937/jaes18-23002
|View full text |Cite
|
Sign up to set email alerts
|

Strength of aged wood in old constructions

Abstract: The results of comprehensive research into spruce and pine wood in a structure after 70 years of its exploitation are presented. Signifi cant changes in the wood in terms of compressive strength along the grain and static bending across the grain were revealed compared with fresh wood. The magnitude of these changes depends on the location of wood in the walls of the structure relative to the cardinal points.Key words: spruce and pine wood, equilibrium moisture content, specifi ed moisture content, ultimate co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…Wood aged in old structures differs in its physical and mechanical properties from fresh wood [14]. Artificially accelerated aging tests can simulate the aging of wood and save time.…”
Section: Introductionmentioning
confidence: 99%
“…Wood aged in old structures differs in its physical and mechanical properties from fresh wood [14]. Artificially accelerated aging tests can simulate the aging of wood and save time.…”
Section: Introductionmentioning
confidence: 99%
“…Material testing, calibration, and analysis are the essential processes in the material and structural characterizations of materials that are possibly subjected to various loads in technical applications [1][2][3][4][5][6][7]. The main material testing variable is hardness, which represents the resistance properties due to deformation and destruction.…”
Section: Introductionmentioning
confidence: 99%
“…Summarizing the relevant research in recent years, it is found that the basic mechanical properties of wood, such as MOE, bending strength, and compressive strength, are affected by factors, such as environmental temperature and humidity, which eventually show changes with use time. For example, Fedyukov et al (2020) have found that the physical properties (compressive strength and flexural strength) of wood structures that have been used for more than 70 years are different from those of new wood, and these changes will have an impact on the structural force performance during the whole life cycle of timber structure. Huang et al (2008) took the old wood replaced during the repair of the Hall of Valor in the Imperial Palace as the test material to study the changes in the physical and mechanical properties of wood structures after more than 100 years of use and found that their physical and mechanical properties changed due to long-term use.…”
Section: Introductionmentioning
confidence: 99%